Recenzja dzieła Beaty Więzowskiej pt. Odpowiedzialność cywilna na zasadzie słuszności, wyd. Oficyna Wolters Kluwer, Warszawa 2009 - Bagińska, Ewa (Studia Iuridica Toruniensia, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–> The monograph by B. Więzowska off ers an incisive analysis of philosophical,theoretical and practical aspects of civil liability based on equity(fairness). The fi rst part of the book is devoted to the philosophical andhistorical origins of the presence of equity, justice and fairness in law. Theauthor accepts the Aristotelian approach to individual justice. In the nextpart she examines the meaning of the term ‘principles of social co-existence’(principles of fariness/justice) and their role in the Polish legal system,with particular focus on the law of civil liability. The Polish approachis compared to the regulations in major continental jurisdictions and incommon law. The second part of the thesis presents the elements andoperation of the principle of fairness in three cases regulated by Polishlaw: public authorities’ liability for legal damage, liability of a minor (in theabsence of the vicarious liability of supervisors) and the liability for animals.The analysis in each chapter starts with comparative remarks regardingthe subject matter liability in major European jurisdictions (German,French, Swiss and English). The author provides many insightfuland interesting observations. The last part of the book covers several particularissues, such as contributory negligence, prescription of claims andjurisdictional matters. The monograph is the first comprehensive analysisof the function of equity (fairness) in Polish tort law and it fi lls a gap in thePolish legal writing. <!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:Standardowy; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –><!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:Standardowy; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>